The reality of Qualifying and Training Graduates of the Department of Library and Information Science - Sana’a University in line with the requirements of the labor market: Field study - Al-Assal, Merzah Ahmed (Journal of Humanities & Social Sciences, 2023)
The study aims to identify the reality of qualifying and training graduates of the Department of Library and Information Science - Sana’a University during university studies and after graduation to be qualified and able to face the challenges and difficulties they may face when searching for a suitable job opportunity and joining the labor market, The researcher relied on the field survey method, A questionnaire was designed and distributed to a random sample of 320 male and female graduates from out of (2666) male and female graduates over a period of (21) years, The study reached a number of results, that there is a need for graduates for more qualification, training, development, acquisition of basic professional skills and more knowledge and understanding of specialization, The lack of scientific qualification and current vocational training was the main reason for not getting a job among library graduates, as well as the lack of interest of the competent authorities in the country in the specialization of libraries and the lack of graduate qualifications with the needs of the labor market was one of the most important reasons for the lack of suitable job opportunities for graduates, in addition to the presence of many challenges, difficulties and problems that hinder the participation of graduates of the Department of Library and Information Science in the labor market, Among the most important recommendations of the study is the development of graduates’ skills of all kinds by intensifying qualification, training and development programs during and after university studies, so that the department’s outputs are strong and required to work in any field, and the development of postgraduate programs in the department, and not being satisfied with the courses studied during the four years. And searching for training and qualifying courses for postgraduate students to keep abreast of everything new in the field of specialization.